2021
DOI: 10.3390/earth2040052
|View full text |Cite
|
Sign up to set email alerts
|

The Health of the Water Planet: Challenges and Opportunities in the Mediterranean Area. An Overview

Abstract: According to the United Nations (2020), since the 1980s, the global overall rate of water use has grown by 1% per year, and it is projected that, by 2050, humanity’s water footprint could exceed 30% of current levels. This situation is in stark contrast to the path toward the Sustainable Development Goals, especially Goal 6, “clean water and sanitation”, which also influences Goal 14, “life below water”, and Goal 15, “life on land”. This is because the availability of water directly affects the food security a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Increasing stress on water resources, competition between water users-industrial, agricultural, and municipal users, as well as nations that share water bodies-is growing (Becken, 2014;Cosgrove & Loucks 2015). Previously published data showed that Qatar, Israel, and Lebanon are experiencing -extremely high‖ levels of water stress, with irrigated agriculture, industries, and municipalities consuming over 80% of their available supply each year on average (Frumkin et al, 2020;Vinci et al, 2021). Pakistan is estimated to reach absolute water scarcity by 2025.…”
Section: Eco-industrial Parks (Eips) In Developing Countriesmentioning
confidence: 99%
“…Increasing stress on water resources, competition between water users-industrial, agricultural, and municipal users, as well as nations that share water bodies-is growing (Becken, 2014;Cosgrove & Loucks 2015). Previously published data showed that Qatar, Israel, and Lebanon are experiencing -extremely high‖ levels of water stress, with irrigated agriculture, industries, and municipalities consuming over 80% of their available supply each year on average (Frumkin et al, 2020;Vinci et al, 2021). Pakistan is estimated to reach absolute water scarcity by 2025.…”
Section: Eco-industrial Parks (Eips) In Developing Countriesmentioning
confidence: 99%
“…216 [27], [28], [29], [30] Data for producing maps of basic fertilizers 1600 [31] Data for production maps of fertilizer in the phenophase 30-34 3 -Data for determining heights of crops 846 [32], [33], [34], [35] Data for estimating the extent of diseases or damages (losses) 2 850 [36], [37] Data for monitoring hydrological stresses 426 [38], [39], [40] Data for producing exact information about climatic changes 2650 [18], [41], [42], [43], [44] Data for identification parcels for potential land for biomass production 146 -Data for creating flood maps (for Q5,25,50,100years) 1230 [45], [46], [47] Data for annual soil erosion risk maps 250 if special search "soil erosion" [48], [49] Data to produce maps of the occurrence of diseases 1750 special search [50], [51] Data for the production of actual calamities map (droughts, flood, fires, earthquakes, ...) 37 [45], [52], [53] Data for production maps of relevant information for biofuel production 248 [54], [55], [56], [57] Data for determining productivity of grassland and pastures. 205 [58], [59], [60] Data for support of the Common Agricultural Policy new 'greening' rules, crop, ecologically sensitive areas 127 [61] Data for the identification of crops to control subsidies 1110 -Data for water protection against nitrates 1130 …”
Section: Number Of Publications Analysed In Mdpi Most Relevant Papersmentioning
confidence: 99%
“…Most conventional strategies used for wastewater treatment, such as chemical precipitation, membrane separation, ion exchange, and electrochemical treatments, present limitations which make their scaling up difficult, thus discouraging their application in real contexts in which large water volumes have to be treated, preferably with simple and low-cost procedures based on reusable materials, allowing for reductions in the required time and costs [9][10][11][12][13]. Chemical precipitation, for example, despite being an economical method, requires additional costs for the disposal of the large quantities of sludge produced during the purification process itself [14].…”
Section: Introductionmentioning
confidence: 99%